Risk and return in commodity futures markets - Outinen, Samuli (My University, 2007)
This thesis investigates the relationship between commodity futures betas and realized returns. This study tries to answer three following questions, do commodity futures embody systematic risk as measured within the context of the Capital Asset Pricing Model? Are returns on commodity futures significantly different from zero? Are the returns on futures positions commensurate with the systematic risk of those positions? This study focuses both single commodity futures and commodity futures as groups. Study contains nine different groups, agricultural, fertilizer, energy, animals, metals, grains and oilseeds, interest rates, index and currency futures. The results are also presented from physical and financial category side. Interest rate, index and currency futures are in financial category and it contains nine different commodity futures. The data consist of 42 different commodities and market portfolio which is constructed from 90% of S&P500 and 10% of Dow-Jones Industrial Average. The period of the study expands from January 1987 to December 2006 and the analysis uses daily and yearly observations of the data. The thesis includes more than 181,000 observations. The empirical results indicate that futures returns are more often positive than negative. Only one was found to have statistically significant positive return, S&P500 index futures. 37 futures had positive and only 5 negative returns. In the case of systematic risk, 28 positive and 14 negative betas were found. Relationship between systematic risk and realized return were equally positively and negatively related and the levels of systematic risk were found to be very low.
Keywords: risk; return; capital asset pricing model; commodity futures.; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|